Manifestations of psychological deformation in modern Kazakh prose (Eurasian Journal of Philology Science and Education, 2021)
Literature is not an ambiance in which everyone can innovate new information . Literature is the mirror of society. The article includes T. Nurmaganbetov’s «Ata konys», M. Magauin’s «Kos agash», A. Altai’s «Killer sauskan», N. Dautaevich’s «Kankyzyl zhalkyn», which depicts the nature, character, customs and essence of the nation in a contaminated way, combining several plots around one plot. ... », D.Kuat’s« Stone bath », O.Bokei’s« Atau-kere »., Writers concerned about the change in national values over time and offered a way for generations in the literary way. The more we look at the above works from a psychological and philosophical point of view, the more we become aware of ethno-deformational changes. Psychologically deformed images are often found in modern Kazakh prose. There are many reasons for this. The above works describe deviations of national consciousness in the psychology of the protagonist and their causes. In addition, the nature of the split in consciousness, which was not previously in our original literature, is a manifestation of psychological deformation in Kazakh prose. Not much has been studied about this in the literature. Although manifestations of ethno deformation in Kazakh prose were observed in the literature of each period, no special classification was carried out. The term ethno deformation has a special meaning in the study of modern Kazakh prose and psychology in prose. The article presents the results of research and analysis of manifestations of psychological deformation in modern Kazakh prose.